If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 4(3 + -1n) = 0 -5 + (3 * 4 + -1n * 4) = 0 -5 + (12 + -4n) = 0 Combine like terms: -5 + 12 = 7 7 + -4n = 0 Solving 7 + -4n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4n = 0 + -7 -4n = 0 + -7 Combine like terms: 0 + -7 = -7 -4n = -7 Divide each side by '-4'. n = 1.75 Simplifying n = 1.75
| y=ln(5x^3) | | 8d^2+30d+25=0 | | -3x+-10x-14=-12 | | (3n+6)(n-2)=0 | | 5-6=3.75 | | 2.8+7=4.8+89 | | 3x=9x-10 | | 42=3y+9 | | 7(-5x+3)=126 | | 7m+4(m-8)= | | log(x^5)-log(x^2)=3 | | -10(s+2)=48 | | 6(2x+4)=25x+250 | | A^2+4a=o | | 0.1(x-7)=3.5 | | y+(-10)=-2(x-5) | | p=6x+2 | | p=6x+1 | | 6789=4 | | -3x+6=x^2+8x+16 | | 0.4x-0.5(2x+3)=0.7(x+3) | | -(2x-4)-(8x-5)+14=-10x(x-1)-(5x+10)+3 | | lnx^5-lnx^2=3 | | P+13=-42 | | 5s+8=48 | | 5x+14=-91-10 | | 5(2x-9)+7x= | | 3p+2p+4y+5y= | | 4x+5=4x-28 | | 31-2x=10-9x | | -(2x-3)-(2x-6)+5=-6(x-1)-(2x-7)+3 | | (3t^2+6t)+(-9t^2-5t+5)= |